Mitigation of Elasmobranch Bycatch in Trawlers: A Case Study in Indian Fisheries - Gupta, Trisha; Booth, Hollie; Arlidge, William; Rao, Chetan; Manoharakrishnan, Muralidharan; Namboothri, Naveen; Shanker, Kartik; Milner-Gulland, E. J. (Frontiers in Marine Science, 2020)
Bycatch poses a significant threat to marine megafauna, such as elasmobranchs. India has one of the highest elasmobranch landings globally, through both targeted catch and bycatch. As elasmobranchs contribute to food and livelihood security, there is a need for holistic approaches to bycatch mitigation. We adopt an interdisciplinary approach to critically assess a range of hypothetical measures for reducing elasmobranch capture in a trawler fishery on India’s west coast, using a risk-based mitigation hierarchy framework. Data were collected through landing surveys, interviews and a literature review, to assess the following potential management options for their technical effectiveness and socio-economic feasibility: (1) Spatio-temporal closures; (2) Net restrictions; (3) Bycatch reduction devices (BRDs) and (4) Live onboard release. Our study provides the first evidence-based and nuanced understanding of elasmobranch bycatch management for this fishery, and suggestions for future conservation and research efforts. Onboard release may be viable for species like guitarfish, with moderate chances of survival, and was the favored option among interview respondents due to minimal impact on earnings. While closures, net restrictions and BRDs may reduce elasmobranch capture, implementation will be challenging under present circumstances due to the potentially high impact on fisher income. Interventions for live release can therefore be used as a step towards ameliorating bycatch, while initiating longer-term engagement with the fishing community. Participatory monitoring can help address critical knowledge gaps in elasmobranch ecology. Spatio-temporal closures and gear restriction measures may then be developed through a bottom-up approach in the long term. Overall, the framework facilitated a holistic assessment of bycatch management to guide decision-making. Scaling-up and integrating such case studies across different species, fisheries and sites would support the formulation of a meaningful management plan for elasmobranch fisheries in India.